TERTIARY STUDENTS' ACADEMIC CHEATING IN PALEMBANG BASED ON SELF-REPORTING CHEATING SCALE (SRCS) - Muhamad Uyun; Idi Warsah (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
This study aimed to determine students’ behavior, especially at three campuses in Palembang, regarding academic cheating. This study used a mixed approach. The samples incorporated students of three campuses, namely UIN Raden Fatah, Universitas Sriwijaya, and Universitas Bina Darma Palembang, with a total of 612 students. The data comprised both qualitative and quantitative data. Academic cheating was measured using the self-reporting cheating scale (SRCS) developed by Newstead and adopted by Lim with a total of 20 items having been adapted as to reveal the quantitative data, while the qualitative data were obtained from interviews and observations. This study concluded that cheating behavior was demonstrated by working together with other students to get answers during quizzes and exams, collaborating with other students to complete individual assignments, doing other students’ assignments, writing out by quoting from books or other publication media without including references properly, concluding or summarizing others’ written works without including the authors as references, and allowing ones’ own works to be copied or imitated by other students. AbstrakPenelitian bertujuan untuk mengetahui perilaku mahasiswa khususnya di tiga kampus Palembang tentang kecurangan akademik. Penelitian menggunakan pendekatan kualitatif deskriptif. Sampel menggunakan tiga (3) tiga kampus yaitu UIN Raden Fatah, Universitas Sriwijaya, dan Universitas Bina Darma Palembang dengan jumlah Responden 612 mahasiswa. Penelitian ini menggunakan pendekatan gabungan. Data terdiri dari data kualitatif dan data kuantitatrif. Kecurangan akademik diukur menggunakan skala self reporting cheating scale (SRCS) yang dikembangkan dari Newstead dan diadopsi oleh Lim dengan jumlah 20 item yang sudah diadaptasi sebagai data kuantitatifnya sedangkan data kualitatif adalah data yang diperoleh dari intervie dan observasi. Penelitian ini memperoleh simpulan bahwa perilaku curang yaitu bekerjasama dengan mahasiswa lain untuk mendapatkan jawaban pada saat kuis maupun ujian, bekerjasama dengan mahasiswa lain untuk menyelesaikan tugas individual, mengerjakan tugas untuk orang lain, membuat tulisan dengan mengutip dari buku atapun media publikasi lainnya tanpa mencantumkan sumber referensi, menyimpulkan ataupun merangkum tulisan orang lain tanpa mencantumkan pengarang sebagai referensi dan mengizinkan tulisan sendiri untuk disalin ataupun dicontoh oleh mahasiswa lain.